2020
DOI: 10.3390/ijerph17197294
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Composition, Physical Activity, Food Intake and Bone Status in German Children and Adolescents

Abstract: Achieving a high bone mass during childhood and adolescence is important for the prevention of osteoporosis in later life. Herein, the purpose was to assess the relationship of various lifestyle factors and bone outcomes in school children. In 248 girls (13.4 ± 1.9 years, BMI: 20.2 ± 4.8 kg m−2) and 231 boys (13.6 ± 1.7 years, BMI: 19.3 ± 3.3 kg m−2), bone mass (stiffness index, SI; calcaneal quantitative ultrasonometry), body composition (bioelectrical impedance analysis), food intake (food frequency question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Bone mass was tested by quantitative ultrasound (QUS), a method of estimating bone status by measuring the velocity and attenuation of ultrasound. QUS is particularly adaptable to evaluating bone mass in epidemiological studies with a relatively large number of healthy children and adolescents, due to its portable, low-cost, and radiation-free advantages, compared to the gold standard method of dual-energy X-ray absorptiometry (DXA) [ 22 , 23 , 24 ]. Studies revealed that the calcaneal QUS is a useful surrogate method for bone mass assessment and has a moderate to excellent correlation (r = 0.60–0.84) with DXA in the pediatric population [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bone mass was tested by quantitative ultrasound (QUS), a method of estimating bone status by measuring the velocity and attenuation of ultrasound. QUS is particularly adaptable to evaluating bone mass in epidemiological studies with a relatively large number of healthy children and adolescents, due to its portable, low-cost, and radiation-free advantages, compared to the gold standard method of dual-energy X-ray absorptiometry (DXA) [ 22 , 23 , 24 ]. Studies revealed that the calcaneal QUS is a useful surrogate method for bone mass assessment and has a moderate to excellent correlation (r = 0.60–0.84) with DXA in the pediatric population [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, when we look in detail at our study participants´ characteristics, we do have to state that most of them were healthy, normal weight, breastfed, and vitamin D supplemented during infancy, and stayed outside on a regular basis. Their diet can be regarded as adequate [further details about their diet can be found elsewhere (Heydenreich et al 2020)]. Therefore, it can be supposed that their lifestyle is favorable for bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Four hundred and eighty-six schoolchildren from six secondary schools of different school types in or close by to Schwäbisch Gmünd, Germany, and their respective parents participated in the study. Further information about recruitment process can be found elsewhere (Heydenreich et al 2020). Measurements were conducted between June 2010 and July 2011.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations